Measuring inspiration in educators: the Educator Inspire Scale (EIS). Issue 3 (27th May 2022) - Lambie, Glenn W.; Tabet, Saundra M.; Stickl Haugen, Jaimie
ABSTRACT: In response to the absence of an instrument to measure educator inspiration with evidence of validity and reliability, the authors developed the Educator Inspire Scale (EIS), an assessment designed to assess the construct of inspiration in educators. Therefore, their investigation examined the psychometric properties of the EIS scores through a two-part study. In Study 1, they constructed and disseminated the 70-item EIS to a developmental sample ( N = 763) of educators and educators-in-training. Using an exploratory factor analysis, they examined the EIS for the most parsimonious factor structure and optimal-scale length. In Study 2, they administered the reduced 19-item EIS to a validating sample ( N = 1015) to establish an internal factor structure through confirmatory factor analysis. Results from both studies purport EIS scores fit a 19-item EIS, four-factor oblique measurement model with 86.4% of explained variance across factors of (a) Motivational Leadership, (b) Empathy, (c) Resilience, and (d) Passion .